2016
DOI: 10.1007/s00405-016-3961-1
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis associated volatile sulphur compound levels in patients with laryngopharyngeal reflux

Abstract: Previous reports have suggested that laryngopharyngeal reflux (LPR) may cause halitosis. However, it remains unclear if LPR is a risk factor for halitosis. The aim of this study was to investigate if patients diagnosed with LPR have an increased probability of halitosis compared to a normal population. Fifty-eight patients complaining of LPR symptoms and 35 healthy subjects were included in the study. A LPR diagnosis was made using an ambulatory 24-h double pH-probe monitor, which is the gold standard diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…66,78,82 The RFS does not take into consideration many LPR findings, including vocal fold erythema, leukoplakia, posterior pharyngeal wall inflammation, anterior pillars inflammation, and coated tongue. 3,79,80,83 Some LPR signs are described in Figure 3 . Second, the RFS allows a subjective evaluation of some signs without clear definition of the rating, which can be a factor explaining the low interreliability among judges.…”
Section: Discussionmentioning
confidence: 99%
“…66,78,82 The RFS does not take into consideration many LPR findings, including vocal fold erythema, leukoplakia, posterior pharyngeal wall inflammation, anterior pillars inflammation, and coated tongue. 3,79,80,83 Some LPR signs are described in Figure 3 . Second, the RFS allows a subjective evaluation of some signs without clear definition of the rating, which can be a factor explaining the low interreliability among judges.…”
Section: Discussionmentioning
confidence: 99%
“…According to 98% of our patients, the RSS completely assessed their complaints that could have been associated with LPR. The RSS has the advantage of including some common symptoms associated with LPR, such as odynophagia, 24 throat pain, 25 tongue burning, 26 nausea, 1 and halitosis, 27 which had been ignored in previous PRO questionnaires. 1 As demonstrated in the present study, the inclusion of these symptoms makes sense in regard to their prevalence in LPR patients and their related impact on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Using an industrial procedure to measure odor intensity (Lang, Farber, Beck, & Yerman, ), they found that VRSs are indeed produced in the oral cavity in halitosis, and they identified mainly VSCs, in particular methyl mercaptan (CH 3 SH) and hydrogen sulfide (H 2 S) (Tonzetich & Richter, ). Since then, dozens of scientific reports using state‐of‐the‐art technologies (chromatography, spectrometry, and different chemical gas sensors) have confirmed the presence of measurable exhaled VSCs and their potential as non‐invasive biomarkers for the diagnosis and monitoring of halitosis (Avincsal et al., ; Coli & Tonzetich, ; Koshimune et al., ; Rosenberg, Kulkarni, Bosy, & McCulloch, ; Van den Velde, Quirynen, van Hee, & van Steenberghe, a; Waler, ; Yaegaki & Sanada, b).…”
Section: Volatile Sulfuric Compounds: From Bad Smell To Potential Biomentioning
confidence: 99%
“…Indeed, studies have shown increased levels of volatile sulfuric compounds (VSCs), which have been measured in the oral cavity and exhaled breath of patients with halitosis. Linked to bacterial activity and produced by local microbial‐enzymatic breakdown of amino acids and other mechanisms, exhaled VSCs have been proposed as biomarkers for diagnosis and monitoring of halitosis (Avincsal et al., ; Aydin, Bollen, & Ozen, ; Kapoor et al., ; Laleman, Dadamio, De Geest, Dekeyser, & Quirynen, ).…”
Section: Introductionmentioning
confidence: 99%